1987
DOI: 10.1128/aac.31.10.1497
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic studies on antibiotic A47934

Abstract: A47934, a peptide antibiotic produced by Streptomyces toyocaensis, belongs to the glycopeptide class of compounds which includes ristocetin and vancomycin. Incorporation studies with radioisotope-labeled substrates indicated that tyrosine, p-hydroxyphenylglycine, p-hydroxyphenylglyoxylate, acetate, and sulfate were efficiently incorporated into A47934. This is consistent with the reported biosynthesis of other glycopeptide antibiotics. Prototrophic mutants blocked in antibiotic biosynthesis were isolated at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
13
0
3
Order By: Relevance
“…toyocaensis A47934 produces the non-glycosylated "glycopeptide" A47934 which comprises the sulfated core heptapeptide of teicoplanin [27,130]. Because A47934 contains no sugar residues, it is a convenient starting scaVold for the addition of sugar residues to generate novel glycopeptides.…”
Section: Streptomyces Toyocaensis A47934mentioning
confidence: 99%
“…toyocaensis A47934 produces the non-glycosylated "glycopeptide" A47934 which comprises the sulfated core heptapeptide of teicoplanin [27,130]. Because A47934 contains no sugar residues, it is a convenient starting scaVold for the addition of sugar residues to generate novel glycopeptides.…”
Section: Streptomyces Toyocaensis A47934mentioning
confidence: 99%
“…Early structural studies in vancomycin family members showed that all of the Hpg groups in the mature antibiotics were in the D configuration 68. Feeding studies also showed that radiolabeled racemic Hpg may serve as monomers for incorporation into the final glycopeptide 6971. Feeding experiments with 13 C‐labeled tyrosine demonstrated that the aromatic ring of Hpg was derived from the aromatic ring of tyrosine and the α‐carbon atom of tyrosine forms the carboxylic acid carbon atom of Hpg (Scheme ) 69.…”
Section: Enzymatic Formation Of the Nonproteinogenic Amino Acid Momentioning
confidence: 99%
“…In plants, tyrosine, Ldopa, or tryptophan decarboxylases represent a branching point from primary metabolism into secondary metabolic pathways, forming, for example, isoquinoline alkaloids (Kutchan and Zenk 1993;Facchini and De Luca 1994;). In various bacteria, tyrosine, the precursor of L-dopa, and also L-dopa itself, serve also as precursors for the biosynthesis of several antibiotics, such as antibiotic A47934 (Zmijewski et al 1987), lincomycin (Neusser et al 1998) and saframycin (Mikami et al 1985). The close proximity to PKS (ca.…”
Section: Resultsmentioning
confidence: 99%